CONSERVATIVE APPROACH IN THE TREATMENT OF CONGENITAL SCOLIOSIS IN ADOLESCENTS: NARRATIVE LITERATURE REVIEW (CIPEEX, 2024)
INTRODUCTION: CONGENITAL SCOLIOSIS (CS) IS A DEFORMITY RESULTING FROM VERTEBRAL FORMATION OR SEGMENTATION DEFECTS, WHICH CAN LEAD TO LIMITATIONS IN DAILY ACTIVITIES AND AFFECT THE QUALITY OF LIFE. TREATMENT INCLUDES NON-INVASIVE APPROACHES, IMPORTANT FOR AVOIDING THE NEED FOR SURGERY, ESPECIALLY DURING THE PUBERTAL GROWTH SPURT. OBJECTIVE: TO DEMONSTRATE THE PHYSIOLOGICAL CHANGES THAT CS CAUSES, WORSENING DURING ADOLESCENCE, AND HOW PHYSIOTHERAPEUTIC TREATMENT BRINGS SIGNIFICANT IMPROVEMENTS TO THE PATIENT. METHODOLOGY: THIS CONSTITUTES A NARRATIVE LITERATURE REVIEW, CONDUCTING SEARCHES IN THE SCIELO, PUBMED, AND RESEARCHGATE DATABASES, CONSIDERING STUDIES PUBLISHED FROM 2015 ONWARDS IN ENGLISH AND PORTUGUESE LANGUAGES. RESULTS: PHYSIOTHERAPEUTIC TREATMENT, SUCH AS THE USE OF THE GLOBAL POSTURE REEDUCATION METHOD AND PILATES, IS RECOMMENDED TO SLOW THE PROGRESSION OF SCOLIOSIS AND AVOID SURGERY. THESE APPROACHES TAKE INTO ACCOUNT INDIVIDUAL PATIENT REQUIREMENTS AND IMPROVE BODY FUNCTIONALITY AND JOINT MOBILITY. CORRECTING POOR POSTURE DURING ADOLESCENCE IS CRUCIAL TO DELAY COMPLICATIONS CAUSED BY THE DISEASE. CONCLUSION: IT WAS OBSERVED THAT CS IN ADOLESCENTS SHOWS BETTER PROGNOSIS WHEN TREATED EARLY. CONSERVATIVE METHODS HAVE PROVEN TO BE EFFICIENT, TAKING ADVANTAGE OF THE STILL-DEVELOPING SPINAL STRUCTURE IN THIS AGE GROUP. THEREFORE, AN INDIVIDUALIZED APPROACH AIMING TO OPTIMIZE CLINICAL OUTCOMES AND THE PATIENT'S QUALITY OF LIFE IS ESSENTIAL, EMPHASIZING THE EFFECTIVENESS OF PHYSIOTHERAPEUTIC INTERVENTIONS.
Keywords: Adolescent; Congenital Scoliosis; Non-invasive Treatment; Physiotherapy